Molecular mechanisms and therapeutic possibilities of short-chain fatty acids in posttraumatic stress disorder patients: a mini-review - Petakh, Pavlo; Duve, Khrystyna; Oksenych, Valentyn; Behzadi, Payam; Kamyshnyi, Oleksandr (Frontiers in Neuroscience, 2024)
This mini-review explores the role of short-chain fatty acids (SCFAs) in posttraumatic stress disorder (PTSD). Highlighting the microbiota-gut-brain axis, this study investigated the bidirectional communication between the gut microbiome and mental health. SCFAs, byproducts of gut microbial fermentation, have been examined for their potential impact on PTSD, with a focus on molecular mechanisms and therapeutic interventions. This review discusses changes in SCFA levels and bacterial profiles in individuals with PTSD, emphasizing the need for further research. Promising outcomes from clinical trials using probiotics and fermented formulations suggest potential avenues for PTSD management. Future directions involve establishing comprehensive human cohorts, integrating multiomics data, and employing advanced computational methods, with the goal of deepening our understanding of the role of SCFAs in PTSD and exploring microbiota-targeted interventions.